A Comparative Evaluation on Online Learning Approaches using Parallel Coordinate Visualization - Kwon, Bum Chul; Lee, Bongshin (Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
As visualizations are increasingly used as a storytelling medium for the general public, it becomes important to help people learn how to understand visualizations. Prior studies indicate that interactive multimedia learning environments can increase the effectiveness of learning [11]. To investigate the efficacy of the multimedia learning environments for data visualization education, we compared four online learning approaches 1) baseline (i.e., no tutorial), 2) static tutorial, 3) video tutorial, and 4) interactive tutorial-through a crowdsourced user study. We measured participants' learning outcomes in using parallel coordinates with 18 tasks. Results show that participants with the interactive condition achieved higher scores than those with the static and baseline conditions, and reported that they had a more engaging experience than those with the static condition.